PENGARUH PENERAPAN STRATEGI PEMECAHAN MASALAH DALAM PEMBELAJARAN MATEMATIKA TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS IX SMP NEGERI 26 PEKANBARU - Husna '; Zuhri D '; Suhermi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine the influence of the implementation of problem solving strategy in mathematics learning to the mathematical problem solving ability of students. This study was conducted in SMP Negeri 26 Pekanbaru on odd semester academic year 2015/2016. This is a pre-experimental study which using the static-group comparison design. The population is all of students at grade IX in SMP Negeri 26 Pekanbaru and the number of sample in this study is 75 students. The sample was determined by using purposive sampling and random sampling tehnique, so that class IX.4 consisting of 36 students as control class and class IX.6 consisting 39 students as experimental class. The experimental class was implemented the problem solving strategy in mathematics learning, meanwhile the control class was implemented conventional learning. The data in this study consisted of qualitative and quantitative data. The qualitative data consisting of observation result, meanwhile the quantitative data consisting of posttest. The data was collected by using observation, test and documentation tehnique. The result showed that the problem solving strategy in mathematics learning influences the mathematical problem solving ability of students at class IX in SMP Negeri 26 Pekanbaru. The level of that influence is 43,06% on medium level.Key Words: Problem Solving Strategies, Mathematics Learning, Mathematical Problem Solving Ability